2013
DOI: 10.1371/journal.pone.0066475
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Eutrophication Induced Shifts in Northern Summer Plankton Communities

Abstract: Marine ecosystems are undergoing substantial changes due to human-induced pressures. Analysis of long-term data series is a valuable tool for understanding naturally and anthropogenically induced changes in plankton communities. In the present study, seasonal monitoring data were collected in three sub-basins of the northern Baltic Sea between 1979 and 2011 and statistically analysed for trends and interactions between surface water hydrography, inorganic nutrient concentrations and phyto- and zooplankton comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
158
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(179 citation statements)
references
References 45 publications
19
158
1
1
Order By: Relevance
“…In contrast, increasing biomass with warming was found for 2 experimental early summer blooms (Taucher et al 2012, Lewandowska et al 2014, as well as for a Baltic Sea long-term field study (1979− 2011) by Suikkanen et al (2013). In summer conditions, nutrient concentrations are naturally low.…”
Section: Growth and Biomass Of Phytoplanktonmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, increasing biomass with warming was found for 2 experimental early summer blooms (Taucher et al 2012, Lewandowska et al 2014, as well as for a Baltic Sea long-term field study (1979− 2011) by Suikkanen et al (2013). In summer conditions, nutrient concentrations are naturally low.…”
Section: Growth and Biomass Of Phytoplanktonmentioning
confidence: 88%
“…Warming under such conditions has a positive effect on phytoplankton biomass. Suikkanen et al (2013) also suggested that warming was the key environmental factor explaining the general increase in total phytoplankton biomass in northern summer Baltic Sea communities in recent decades.…”
Section: Growth and Biomass Of Phytoplanktonmentioning
confidence: 99%
“…Regular monitoring of the Baltic Sea over the past 100 years has indicated higher rates of temperature increase (0.08 to 0.11 • C per decade) than the global average, along with a 20 % decrease in annual maximum ice extent (HELCOM, 2013). Observed shifts in the spring and summer phytoplankton community dynamics have been primarily associated with warming in northern Baltic Sea regions over the past three decades (Suikkanen et al, 2013).…”
Section: A J Paul Et Al: Effect Of Elevated Co 2 On Organic Mattermentioning
confidence: 99%
“…The significant increase in SST observed off Karnataka waters would have increased the productivity of phytoplankton which is reflected in the diet composition of mackerel. At a regional scale, increase in SST has shown to increase the phytoplankton biomass in the Baltic Sea (Suikkanen et al, 2013) and in the North Sea (McQuatters-Gallop et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A shift in the food web structure was observed in the Baltic Sea towards more microbial, less energy-efficient food webs consisting of lower food quality and smaller sized organisms, which in combination with warming may lead to decreased availability of energy for grazing zooplankton and fish (Suikkanen et al, 2013). Studies conducted by Klauschies et al (2012) on effects of warming on phytoplankton communities with different light intensities in the Baltic Sea projected that under high temperature and lower light levels a higher share of smaller phytoplankton is expected for the next decades.…”
Section: Introductionmentioning
confidence: 99%